Lemongrass (Cymbopogon citratus) Ethanolic Extract Exhibited Activities That Inhibit -glucosidase Enzymes and Postprandial Blood Glucose Elevation - Gunawan Puteri, Maria Dewi Puspitasari Tirtaningtyas; Tjiptadi, Felicia Melissa; Hendra, Phebe; Santoso, Filiana; Udin, Zalinar; Artanti, Nina; Florence Ignatia, Florence Ignatia (UI Scholars Hub, 2020)
Lemongrass is a common ingredient in Indonesian traditional herbal medicine that potently inhibits carbohydrate hydrolysis. In this study, the in vitro α-glucosidase inhibitory (AGI) activity of lemongrass was compared with its in vivo activity to retard postprandial blood glucose elevation, and the bioactive compounds responsible for these activities were observed. Both water and ethanolic extracts of lemongrass (WLG and ELG, respectively) were tested in vitro for its inhibition of the sucrose and maltose hydrolyzing activities of rat intestinal glucosidase. ELG was observed to exert higher inhibitory activities (Sucrase IC50 = 8.74 mg/mL; Maltase IC50 = 18.93 mg/mL) than WLG. ELG was evaluated for its in vivo activity to retard blood glucose elevation in mice after sucrose, maltose, and glucose consumption. ELG was also fractionated using activity-guided chromatography, followed by liquid chromatography–mass spectrometry and high-performance liquid chromatography (HPLC). In vivo sugar tolerance test confirmed the AGI activity in a non-dose-dependent manner and showed potential additional mechanisms that may prevent postprandial hyperglycemia. The active principles were acquired in methanol-soluble fraction and purified using preparative thin-layer chromatography. HPLC analysis with commercial standards identified caffeic acid and kaempferol as the compounds responsible for the bioactivity of ELG. Results showed that lemongrass has the potential as herbal medicine ingredient in the management of diabetes.